Hungarian Monitoring, 16 November 1989 . [Magyar rádiófigyelő], 1989. november 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Changes in Bulgaria - Kohl government's statement on Eastern European developments - GDR: inter-party agreement on coalition government - New CP general secretary in Moldavia Domestic Affairs: - Hungary's membership request at the Council of Europe - Ministerial council in session: deregulation of education, energy policy, People's Control Committees to be dissolved, monopoly of the post office - Péter Medgyessy in Japan - Hungarian Socialist Workers' Party (MSZMP) on the referendum - Satirical memo on political parties Economy: - Criticism of the tax system Külpolitika: - A bulgáriai változásokról - Kohl kormánynyilatkozata a kelet-európai fejleményekről - NDK: pártközi megállapodás a koalíciós kormányról - Új KP első titkár Moldáviában Belpolitika: - Magyarország felvételi kérelme az ET-ban - Minisztertanács ülése:közigazgatás deregularizációja, energiapolitika, megszűnik a népi ellenőrzés, a posta monopóliuma, - Medgyessy Péter Japánban - MSZMP a népszavazásról - Szatirikus jegyzet a pártokról Gazdaság: - Az adórendszer kritikája